Biodegradable versus titanium osteosynthesis in maxillofacial traumatology: a systematic review with meta-analysis and trial sequential analysis. Issue 7 (July 2020) - Gareb, B.; van Bakelen, N.B.; Dijkstra, P.U.; Vissink, A.; Bos, R.R.M.; van Minnen, B.
Abstract: Titanium osteosynthesis is currently the fixation system of choice in maxillofacial traumatology. Biodegradable osteosynthesis systems have the ability to degrade in the human body. The aim of this study was to conduct a systematic review, with meta- and trial sequential analyses, to assess the efficacy and morbidity of biodegradable versus titanium osteosynthesis after maxillofacial trauma. MEDLINE, Embase, and CENTRAL were searched for randomized controlled trials and prospective and retrospective controlled studies. Five time periods were studied: perioperative, short-term (0–4 weeks), intermediate (6–12 weeks), long-term (>12 weeks), and overall follow-up. After screening 3542 records, 24 were included. All had a high risk of performance and detection bias due to the nature of the interventions. Meta-analysis showed no differences in efficacy or morbidity between biodegradable and titanium osteosynthesis. The risk of perioperative screw breakage was significantly higher (risk ratio 17.13, 95% confidence interval 2.19–34.18) and the symptomatic plate removal rate lower in the biodegradable group (risk ratio 0.11, 95% confidence interval 0.02–0.57), which was confirmed by the trial sequential analysis. The quality of evidence ranged from very low to moderate. Based on the narrative review and meta-analyses, current evidence shows that biodegradable osteosynthesis is a viable alternative to titanium osteosynthesis when applied in the treatment of maxillofacial trauma, with similar efficacy but significantly lower symptomatic plate removal rates. Perioperative screw breakage occurred significantly more often in the biodegradable group compared to the titanium group.